Komunikasi Orang Tua Tentang Seksualitas Terhadap Perilaku Seksual Pranikah Pada Remaja - Isna Wanufika; Sumarni Sumarni; Djauhar Ismail (Fakultas Kedokteran Universitas Gadjah Mada, 2017)
Parents' communication about sexuality to premarital sexual behavior in adolescentsPurposeThis research aimed to examine the relationship between parent-child communication about sexuality and adolescents premarital sexual behavior.MethodsThis research involved 205 students in Senior High School